PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PERAWAT DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - Lousyiana1, Tiara Thita (Jurnal Tepak Manajemen Bisnis, 2015)
Abstract. This study aims to determine the relationship of leadership style and organizational culture to job satisfaction and performance of nurses Ibnu Sina Islamic Hospital Pekanbaru. The population in this study included all nurses Ibnu Sina Islamic Hospital Pekanbaru, amounting to 196 people. The primary data were collected by questionnaire as the instrument to prove the result of the study, to test the hypotheses using path analysis with SPSS. Sampling technique chosen is cluster sampling (104 nurses Ibnu Sina Islamic Hospital pekanbaru as samples).The results showed that: 1) The leadership style directly influence the performance of nurses Ibnu Sina Islamic Hospital, 2) Relationship of leadership style to the performance is not directly through job satisfaction nurses, so it can be concluded that job satisfaction is a strong mediating variable between leadership style on nurses performance, 3) Organizational culture directly do not have significant effect on the performance of nurses, 4) Through job satisfaction, organizational culture have positive and significant impact on the performance of nurses, it can be concluded, job satisfaction have an important role in mediating relations between organizational culture on the performance of nurses, 5) Job satisfaction directly influence the performance of nurses Ibnu Sina Islamic Hospital.Keyword : leadership style, organizational culture, job satisfaction, the performance of nurses